Ball possession strategies in elite soccer according to the evolution of the match-score: the influence of situational variables - Lago-Penas, C.; Dellal, A. (Journal of Human Kinetics, 2010)
In soccer, the ability to retain possession of the ball for prolonged periods of time has been suggested to be linked to success. The accuracy of this assertion was investigated by examining 380 matches involving Spanish League First Division teams during the 2008-2009 season. Possession of the ball, according to the status of the match (winning, drawing and losing), was recorded during the different matches using a multiple-amera match analysis system (GecasportR). The results suggest that the best classified teams maintained a higher percentage of ball possession and that their pattern of play was more stable. The coefficient of variation, with respect to ball possession per match, was smaller for the best placed teams. Indeed, first placed F.C. Barcelona had the smallest coefficient of variation for possession time (8.4%), while bottom placed Recreativo showed the highest values with 17.1%. Linear regression analysis showed that possession strategies were influenced by situation variables. Team possession was greater when losing than when winning (p<0.01) or drawing (p<0.01), home teams enjoyed greater possession than visiting teams (p<0.01), and playing against strong opposition was associated with a reduction in time spent in possession (p<0.01). The findings indicate that strategies in soccer are influenced by situational variables and that teams alter their playing style accordingly during the match.